Risk of hematologic malignancies in psoriasis and rheumatoid arthritis patients using long term TNF-α inhibitors: a retrospective nationwide study - Jihun Song; Seong Rae Kim; Yu-Jin Kim; Sun Jae Park; Seogsong Jeong; Sang Min Park (Scientific Reports)
Abstract This retrospective cohort study included all user of tumor necrosis factor-α inhibitors (TNFi), including etanercept, infliximab, adalimumab, and golimumab, among Korean patients with psoriasis and rheumatoid arthritis (N of user = 7,645) and the non-user who was diagnosed with same diseases, never used TNFi, and was served as the reference. Cumulative usage of TNFi was calculated between the newly diagnosed date and index date (2-year from the diagnosed date). Adjusted hazard ratio (aHR [95% confidence intervals (CIs)]) for colorectal, liver, lung, kidney, breast, and thyroid cancer were not significantly increased or decreased: 0.92 [0.61–1.38], 0.90 [0.53–1.53], 1.00 [0.73–1.37], 1.20 [0.62–2.34], 0.91 [0.62–1.34], and 0.91 [0.66–1.26], respectively. The increased risk of lymphoma in the infliximab user (2.49 [1.33–4.66]; p < 0.01) was statistically significant. Similarly, the risk of leukemia increased significantly in the etanercept (3.87 [1.71–8.76]; p < 0.01) and adalimumab (3.36 [1.65, 6.84]; p < 0.001) user. Accumulated prescriptions of TNFi for two years did not increase the incidence of cancer, except lymphoma and leukemia. Since the use of TNFi increases the risk of leukemia and lymphoma, a decision for frequent prescription of TNF-α inhibitors should be more careful.